Force-velocity profiling among handball-players differences between player-positions - Axell, P.; Öberg, K. (University of Gothenburg, 2020)
Modern handball has an intermittent character which includes several complex physical qualities. Knowledge of these individual physical demands between player positions seems to be essential in order to design optimal training programs to maximize players potential on the pitch. Purpose: investigate if the vertical force-velocity profile is related to player position in elite male team handball and evaluate if there is a significant difference in how players expresses their mechanical power output when comparing pivots and wings. Method: Thirty elite handball players (Wings N=17, Pivots N=13) from Swedish top division handbollsligan performed total eight vertical squat jumps (SJ) with loads ranging from 0-60 % of their bodyweight. Jump height (cm), velocity (m/s), relative force (N/kg), absolute force (N), % imbalance (%imb) and power-max (Pmax) (w/kg) were recorded and analyzed with ascientifically validated iPhone app (MyJump). Results: Jump height is significantly (37.90 cm vs 44.05 cm, SE=2.059, p=0.006) greater among wings but in contrast pivots significantly express more absolute force (3162.15 N vs 2741.17 N, SE=147.93, p=0.008). Wings have higher velocity (2.85 m/s vs 3.19 m/s, SE=0.168, p=0.048) and there is a significant difference between the groups in their Pmax. (22.58 w/kg vs 26.20 w/kg, SE=1.095, p=0.003) Conclusion: It exist a difference between pivot and wings when we compare relative force, absolute force, velocity, Pmax and Jump height. Notable is that wings when performing an unloaded and loaded squat jump are better suited to handle their relative strength (N/kg) compared to pivots who express a higher absolute force (N) .